Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2005)
Welcome to our seventh issue of the Colombian Applied Linguistics Journal. This time we offer a collection of eight articles that illustrate some of the concerns of critical applied linguistics related with praxis, social, cultural and political domains, critical social inquiry and self refl exivity. We believe that the articles in this issue, to a certain extent, address and contextualize these concerns.